ANALISIS FAKTOR INDIVIDU DAN FAKTOR PEKERJAAN YANG BERHUBUNGAN DENGAN PRODUKTIVITAS KERJA USAHA MIKRO, KECIL DAN MENENGAH (UMKM) KULINER PADA PEKERJA PEREMPUAN DI KECAMATAN BABAKAN MADANG KOTA BOGOR - Nabila Fenelia (2022)
In MSMEs in Indonesia, the proportion of female workers is higher than that of male workers. There are various obstacles and risks in a job in the non-formal sector, such as MSMEs, that can affect the work productivity of female workers. Low work productivity affects production as well as the quality and quantity of female workers. The purpose of this study is to analyze individual factors and work factors related to the work productivity of MSMEs in female workers. The research method uses quantitative analysis with a cross-sectional study design. The research subjects were all female workers in MSMEs in Babakan Madang District who found 75 people using the total sampling method. Data analysis used univariate, bivariate with Chi-Square test and multivariate with multiple logistic regression. The results of the bivariate study showed that age (p-value=0.002), attitude (p-value=0.001) and physical work environment (p-value=0.017) had a significant relationship with work productivity. In multivariate analysis, it is known that the age factor (p-value= 0.004; POR= 0.19; 95% CI= 0.06-0.59), which indicates that young age (<25 years) can minimize the risk of being unproductive at work by 0.19 times. It is recommended for young female workers to improve attitudes and communication, build a good physical work environment, and actively participate in OSH training held across related sectors.